Navigating environmental constraints to injection preparation: the use of saliva and other alternatives to sterile water among unstably housed PWID in London - Magdalena Harris; Jenny Scott; Vivian Hope; Talen Wright; Catherine McGowan; Daniel Ciccarone (BMC, 2020)
Abstract Background The United Kingdom is experiencing an increase in drug-related deaths and serious bacterial infections among its most vulnerable citizens. Cuts to essential services, coupled with a growing homeless population, create a challenging environment to tackle this public health crisis. In this paper, we highlight an underexplored environmental constraint faced by people living and injecting drugs on the streets. Access to water for injection is restricted in the UK, due to legislative and financial barriers. Austerity measures, such as public toilet closures, further restrict the ability of people made homeless to access clean water and protect themselves from health harms. Methods We generated questionnaire (n = 455) and in-depth qualitative interview (n = 32) data with people who inject drugs in London for the Care and Prevent study. Participants provided detail on their life history; drug use, injecting and living environments; health conditions and care seeking practices. Findings A high proportion of the survey sample reported lifetime history of street homelessness (78%), bacterial infections (65%) and related hospitalisation (30%). Qualitative accounts highlight unsafe, potentially dangerous, injection practices in semi-public spaces. Multiple constraints to sourcing sterile water for injection preparation were reported. Alternatives to sterile water included puddle water, toilet cistern water, whisky, cola soda and saliva. Participants who injected heroin and crack cocaine together unanimously reported adding water at two stages during injection preparation: first, adding water as a vehicle for heroin (which was then heated); second, adding cold water to the heroin mixture prior to adding the crack cocaine. This new finding of a stage addition of solvent may represent an additional risk of infection. Conclusion Currently, harm reduction equipment and resources for safe injecting are not meeting the needs of people who inject drugs who are street homeless or unstably housed. Preparation of injections with non-sterile water sources could precipitate bacterial and fungal infections, particularly when used without the application of heat. It is crucial that water for injection, also skin cleaning, is made available for the unstably housed and that harm reduction messaging is tailored to speak to the everyday realities of people who prepare and inject drugs in public spaces.